PERTUMBUHAN DAN HASIL KACANG KORO PEDANG PADA APLIKASI PUPUK NPK DAN KOHE SAPI - Abdullah Sarijan; Rangga Kusumah; Nurhening Y E (Musamus University, 2022)
ABSTRACT Sword bean is a type of legume that has not been cultivated intensively. This plant can be developed as a companion or substitute for soybeans in the manufacture of tempeh, vegetable milk, tauco, soy sauce, various snacks, vegetable dishes, and various other processed foods. The production of sword beans is higher than soybeans and has some nutritional content which is also higher than soybeans. This study aims to determine the effect of fertilization on the growth and yield of sword beans. The study was designed in a randomized block design, consisting of three fertilization treatments and six replications. The results showed that fertilization affected the observation of plant height, the number of pods, pod length, and production. The highest production was obtained from the treatment of NPK fertilizer with a yield of 7.9 kg/plot or 3.6 tons/ha Keywords: rakara bedung, mecca nuts, machete nuts